Treinta colombianismos que le faltan al DRAE (Papeles, 2010)
In spite of the constant concern of Colombian linguists, lexicographers and dialectologists to search and register the different new meanings for words and expressions that come and remain in Spanish language spoken in Colombia, thanks to the inventive of the speakers, there are many Colombian terms of general, frequently and daily usage which meaning still do not exist in the DRAE. This problem, firstly, subtracts genuineness and prestige to these words, because their meanings are not recognized on the part of the academic authority, in this case RAE, and secondly, it doesn’t allow those who consult the dictionary to known the lexical wealth of our country. This article is the result of a lexicographical investigation framed in the class of Lexicography of the Master in Spanish Linguistics at Instituto Caro y Cuervo, in which thirty terms of frequent and daily usage are explored in the Colombian lexicon, and that proposes meanings that have not been documented by the DRAE yet.
Keywords: lexicography; dictionary; Colombian expression; entry; meaning; idiom